Treatment of Helicobacter Pylori – an Overview of Current Strategies of Diagnostic and Treatment - Ruxandra BABIUC; Raluca Anica IONESCU; Lucian NEGREANU (Modern Medicine)
Helicobacter Pylori infection, responsible for ulcerous disease, atrophic gastritis, gastric cancer and MALT lymphoma (mucosa-associated lymphoid tissue) has a very high prevalence in the general population (approximately 50%). In Romania there are few data related to the prevalence of Helicobacter Pylori infection, as well as the resistance to antibiotic treatment, and the methods of patient surveillance are limited by costs and low accessibility. The aim of our paper is to recall the current possibilities of treatment and supervision of this category of patients, taking into account that the appropiate treatment and good monitoring of the patient can cure the complications of the disease and may prevent the occurrence of malignancies.